2020
DOI: 10.3390/biology9090257
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Reticuloendotheliosis Virus 5′ Long Terminal Repeat Integration in the Genome of Avipoxvirus Field Strains from Different Avian Species in Egypt

Abstract: Avipoxviruses (APVs) are among the most complex viruses that infect a wide range of birds’ species. The infection by APVs is often associated with breathing and swallowing difficulties, reduced growth, decreased egg production, and high mortalities in domestic poultry. In the present study, 200 cutaneous nodular samples were collected from different avian species (chicken, pigeon, turkey, and canary) suspected to be infected with APVs from Dakahlia Governorate, Egypt. Pooled samples (n = 40) were prepared and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(115 reference statements)
1
5
0
Order By: Relevance
“…The identified REV-LTR sequences showed a high degree of genetic identity (98.8%) with REV- 5′LTR integration identified in fowl poxvirus (FWPV) isolates identified previously in Dakahlia/2017 (MT251362.1) ( Mosad et al, 2020 ) The results indicate the circulation of REV in the Egyptian poultry farms with the possibility of integration of REV in both viruses (FWPV and MDV). the identified REV-LTR sequences showed a high degree of identity (95–98.5%) with identified REV-LTR integrated in FWPV and GaHV from China, USA, South Africa, and Australia, suggesting potential transmission of the virus from these countries.…”
Section: Discussionsupporting
confidence: 55%
“…The identified REV-LTR sequences showed a high degree of genetic identity (98.8%) with REV- 5′LTR integration identified in fowl poxvirus (FWPV) isolates identified previously in Dakahlia/2017 (MT251362.1) ( Mosad et al, 2020 ) The results indicate the circulation of REV in the Egyptian poultry farms with the possibility of integration of REV in both viruses (FWPV and MDV). the identified REV-LTR sequences showed a high degree of identity (95–98.5%) with identified REV-LTR integrated in FWPV and GaHV from China, USA, South Africa, and Australia, suggesting potential transmission of the virus from these countries.…”
Section: Discussionsupporting
confidence: 55%
“…Poxviruses replicate in the cytoplasm of the cell and bud through cellular endocytosis. ( Mosad et al., 2020 ; Deng et al., 2022 ; Walker et al., 2021 ). Avipoxviruses extensively infect nonmammalian hosts including more than 300 species of birds ( Bolte et al., 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with that of CNPV, FWPV infection is a disease with a low mortality proportion, which diminishes egg production and damages growth and fertility. But sometimes, the fatality of fowlpox reaches 50%∼100% without vaccine protection ( Mosad et al., 2020 ; Zhao et al., 2014 ). Therefore, the vaccine is a necessary method for preventing avipoxviruses.…”
Section: Introductionmentioning
confidence: 99%
“…The avian retrovirus, reticuloendotheliosis virus (REV) is known to partially or completely integrate into the genome of some APV viruses and it is believed that the pathogenicity of the APV is enhanced by the presence of the integrated REV [ 8 , 10 , 16 , 20 ]. Reports from commercial flocks suggested that APV vaccine contamination with REV caused tumours in vaccinated birds [ 5 ] while, more recently, an acute outbreak of FP in China which resulted in 100% mortality of commercial chickens was caused by an APV with integrated partial REV sequences [ 22 ].…”
mentioning
confidence: 99%
“…Currently in Africa, APVs have only been genetically characterised in a few countries. These include Egypt [chicken (subclade A1), pigeon (subclade A4), and turkey (subclade A2)], Nigeria [chicken (subclade A1)], Mozambique [chicken (subclade A1 and clade E), peacock (subclade A1), quail (subclade A2) and turkey (subclade A2)], South Africa [dove (subclade A3), flamingo (subclade A3), penguin (subclade A2) and pigeon (subclade A2 and A3)] and Tanzania [chicken (subclade A1)] [ 1 , 4 , 14 , 15 , 16 , 17 ]. As there was no information available on APVs in Namibia this study was undertaken to characterize viral DNA obtained from FP outbreaks in the country.…”
mentioning
confidence: 99%